METHODS AND CRITERIA FOR MEASURING COMPETITIVENESS OF AGRICULTURAL SECTOR - Saidova Dildora Nurmatovna , Ashurmetova Nigora Azatbekovna , Dexkanova Shakhlokhon Sagdiyevna , Mustafayev Sarvar Abdirozzokovich (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research paper presents researches that have made it possible to reveal available methods for assessing the competitiveness of agricultural products, taking into account the natural and climatic conditions of Uzbekistan, which determine the fundamental risks at various stages of the production process.